Clinical benefits of central pancreatectomy for a patient with pancreatic schwannoma and diabetes - Long Cheng Zhao; Zi Ye Li; Fan Wu; Yue Hu; Bai Lin Wang (World Journal of Surgical Oncology)
Abstract Schwannomas are tumors that originate from the glial cells of the nervous system and can occur on myelinated nerve fibers throughout the body, especially in the craniofacial region. However, pancreatic schwannomas are extremely rare. We report a case of a pancreatic schwannoma that was difficult to differentiate from other pancreatic tumors preoperatively. A 44-year-old female patient was found to have a pancreatic mass on Computed Tomography imaging and the preoperative diagnosis was a pancreatic solid pseudopapillary neoplasm. Meanwhile, the patient had type 2 diabetes and the blood glucose was controlled at 8-15mmol/L by taking oral antidiabetic drugs. During exploratory laparotomy, an 8 cm × 7 cm × 4 cm mass was discovered in the middle part of the pancreas. Considering the preoperative diabetes, the patient underwent a central pancreatectomy (CP) and Roux-en-Y pancreaticojejunostomy. Postoperative histopathological examination confirmed the diagnosis of a pancreatic epitheloid schwannoma. After surgery, the patient developed Grade B pancreatic fistula, which disappeared after treatment. At the same time, the patient’s blood glucose remained basically stable by insulin therapy, which was adjusted to oral antidiabetic medications in about 40 days after surgery. At a 32-month follow-up after discharge, no tumor recurrence was observed, and the patient’s blood glucose was controlled below 11.1mmol/L with only oral antidiabetic drugs. The radiological diagnosis of pancreatic schwannomas lacks specific features, and diagnosis primarily relies on histopathological examination and immunohistochemical testing. Although pancreatic schwannomas are extremely rare, they must be differentiated from other solid or cystic pancreatic lesions. For patients with pancreatic schwannoma and diabetes, CP may represent a favorable surgical option.